2007
DOI: 10.1007/s10802-007-9142-3
|View full text |Cite
|
Sign up to set email alerts
|

Joint Attention and Attachment in Toddlers with Autism

Abstract: Joint attention is often referred to as a triadic relation between self, other and object. Young children with autism show deficiencies in the use of joint attention behaviors. Individual differences may be expected, and they may be determined by the children's cognitive development or the characteristics of the relationship of the child with the caregiver. Although most joint attention skills develop under the age of three, most studies of joint attention in children with autism involved children older than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 69 publications
1
23
0
1
Order By: Relevance
“…Both coded each child’s strange situation independently; three disagreements were resolved through discussion. As Naber et al (2007b) noted in conjunction with their own study, when coding disorganization in children with autism, observers should take the individual’s own baseline behavior – as displayed in the first few strange situation episodes – into account, to differentiate between conventionally identified disorganized/disoriented behavior and those anomalous behaviors that are typical for children with autism. A further criterion for assessing the disorganization of attachment, following Pipp-Siegel and colleagues (1999), was whether these behaviors were shown in connection with the mother (upon separation and reunion) or indiscriminately throughout the session.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Both coded each child’s strange situation independently; three disagreements were resolved through discussion. As Naber et al (2007b) noted in conjunction with their own study, when coding disorganization in children with autism, observers should take the individual’s own baseline behavior – as displayed in the first few strange situation episodes – into account, to differentiate between conventionally identified disorganized/disoriented behavior and those anomalous behaviors that are typical for children with autism. A further criterion for assessing the disorganization of attachment, following Pipp-Siegel and colleagues (1999), was whether these behaviors were shown in connection with the mother (upon separation and reunion) or indiscriminately throughout the session.…”
Section: Methodsmentioning
confidence: 98%
“…Though there is an emerging literature on the social and cognitive correlates of attachment in autism (e.g. Capps, Sigman, & Mundy, 1994; Koren-Karie Oppenheim, Dolev, & Yirmiya, 2009, 2007b; Naber et al, 2007a; Oppenheim, Koren-Karie, Dolev & Yirmiya, 2009; Van IJzendoorn et al, 2007; Willemsen-Swinkles, Bakermans-Kranenburg, Buitelaar, van IJzendoorn, & van Engeland, 2000), the implications of secure attachment for subsequent development in children with autism remains an understudied topic (Kahane & El-Tahir, 2015). To that end, the goals of the present study were to (1) investigate the correlates of individual differences in the quality of attachment organization in children with autism, including maternal sensitivity as well as child cognitive and social skills, and, (2) for the first time, examine the implications of attachment security for subsequent development of these children.…”
mentioning
confidence: 99%
“…Clifford and Dissanayake (2008) studied home videos of infants later diagnosed with autism, identifying poor quality and timing of eye contact even during the first year of life. Similarly, 2-year-old infants with autism show less frequent joint attention behaviours (Naber et al, 2007). Thus sharing attention and being able to identify the direction of another persons' gaze, is a core problem for individuals with autism.…”
Section: Running Head: Eye-tracking Gaze Direction and Autismmentioning
confidence: 99%
“…However, Rutgers et al (2004) also revealed that, when compared to groups of typically developing children, secure attachments are significantly underrepresented (medium effect size) in ASD. High levels of ASD symptoms and the presence of intellectual disability seem to significantly reduce the likelihood that a child with ASD will develop secure attachment relations (Rutgers et al 2004; Naber et al 2007b). One interpretation of these findings is that it may take children with ASD more time to form coherent expectations about how caregivers will respond to bids for comfort.…”
Section: Introductionmentioning
confidence: 99%